PENGARUH PEMBERIAN SOLID (TANDAN KOSONG KELAPA SAWIT) DAN ARANG SEKAM PADI TERHADAP PRODUKSI TANAMAN TOMAT - Wizni Fadhillah; Fitra Syawal Harahap (Jurnal Tanah dan Sumberdaya Lahan, 2020)
This study aimed to determine the effect of various types of solid (oil palm empty fruit bunches) and rice husk charcoal on the production of tomato plant (Solanum lycopersicum L). The treatments tested for this study consisted of two factors. The first factor was the provision of solid, i.e. S0 = without solid (control), S1 = 0.50 kg solid polybag-1, S2 = 0.70 kg solid polybag-1, and S3: 1 kg Â solid polybag-1. The second factor was the provision of rice husk charcoal, i.e. P0 = without husk charcoal (control), P1 = 0.2 kg husk charcoal polybag-1, and P2 = 0.4 kg husk charcoal polybag-1. Each polybag contained 5 kg of air-dried soil. The results of this study indicated that the provision of solid and rice husk charcoal against tomato plant production had no significant effect on stem diamater, total number of fruits per plant, and total weight of fruits per plant. However, the treatment interaction of 1 kg solid polybag-1 and 0.2 kg husk charcoal polybag-1 increased stem diameter, total number of fruits per plant, Â and total weight of fruits per plant.